2017
DOI: 10.1080/19336896.2016.1274000
|View full text |Cite|
|
Sign up to set email alerts
|

Are Brazilian cervids at risk of prion diseases?

Abstract: ABSTRACT. Prion diseases are neurodegenerative fatal disorders that affect human and non-human mammals. Chronic Wasting Disease (CWD) is a prion disease of cervids regarded as a public health problem in North America, and polymorphisms at specific codons in the PRNP gene are associated with this disease. To assess the potential CWD susceptibility of South American free-ranging deer, the presence of these polymorphisms was examined in Mazama gouazoubira, Ozotoceros bezoarticus and Blastocerus dichotomus. Despit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…However, the susceptibility of such species to the majority of livestock pathogens is poorly understood. Health studies in South American deer species have mainly focused on serological surveys, e.g., brown brocket deer (BBD; Mazama gouazoubira ) in Bolivia [ 19 ], Argentinean Pampas deer ( Ozotoceros bezoarticus ) [ 20 ], and several studies of free-ranging and captive Brazilian deer populations [ 21 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the susceptibility of such species to the majority of livestock pathogens is poorly understood. Health studies in South American deer species have mainly focused on serological surveys, e.g., brown brocket deer (BBD; Mazama gouazoubira ) in Bolivia [ 19 ], Argentinean Pampas deer ( Ozotoceros bezoarticus ) [ 20 ], and several studies of free-ranging and captive Brazilian deer populations [ 21 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the 23 and 12 bp insertion/deletion polymorphisms located in the promoter region were associated with the expression of the bovine PRNP gene and were reported to affect vulnerability to BSE ( 12 ). Furthermore, genetic polymorphisms at codons 95, 96, and 132 of the cervid PRNP gene played an important role in susceptibility to CWD in the cervidae family ( 13 15 ). Recent studies have reported that prion disease-resistant specific amino acids of PrPs, including S167 in horses and D159 in dogs, conferred resistance to conversion from PrP C to PrP Sc ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, CWD has been detected in captive cervid populations in 18 U.S. states and three Canadian provinces (https://www.usgs.gov/centers/nwhc/science/expanding-distribution-chronic-wasting-disease). Current evidence (Falcão et al 2017; Mawdsley 2020; Buchholz et al 2021; Hannaoui et al 2017; Sohn et al 2002; Hamir et al 2011; Nalls et al 2013; Benestad et al 2016; Vikøren 2019; Cullingham et al 2020; USGS 2021) indicates that CWD occurs in several native North American cervid species, including white-tailed deer ( O. virginianus ), North American elk…”
Section: Introductionmentioning
confidence: 99%